ISOLATION AND STRUCTURE ELUCIDATION OF SECONDARY METABOLITE COMPOUNDS FROM Curcuma aeruginosa - Alsya Firdausi Nuzula; Alfinda Novi Kristanti; Nanik Siti Aminah; Yoshiaki Takaya; Marisa Nur Sahadatin; Andika Pramudya Wardana (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2023)
Black turmeric (Curcuma aeruginosa) is Indonesian medicinal plant belonging to the Zingeberaceae family, mostly found on Java. This study aimed to determine the new molecular structures of the compounds isolated from black turmeric originating from Indonesia. Isolation of the secondary metabolite compounds was initiated by solid-liquid extraction using the maceration method with ethanol solvent, followed by liquid-liquid extraction using the partition method with n-hexane and dichloromethane as solvents. Separation and purification were carried out using vacuum liquid chromatography (VLC) and gravity column chromatography (GCC). The isolated compounds were characterized using spectroscopic methods, including UV-Vis, IR, and NMR spectroscopy. The isolation resulted in three sesquiterpenoid compounds, (E)-7-isopropyl-4,10-dimethylcyclodec-10-ene-5,8-dione (curdione), (1R,10R)-Epoxy-(-)-1,10-dihydrocurdione, and zedoalactone B, together with two common terpenes, ethyl tetradecanoate and 1-hexadecene.